Taking learning to new heights: Exploring ecology, state history, and geology through a field trip to 4, 200 meters (14, 000 feet). (31st March 2021) - Follari, Lissanna; Larsen, Jessi; Marquardt, Christi; Goldman, Maddie
Abstract: Our 4 th grade year has become known as "the field trip year", with over 10 trips carefully aligned with learning units across the year. This article describes the first trip of the year, which in many ways sets the stage for students' effective use of field trips as engaging extensions and applications of classroom learning. The Pike's Peak Summit Trip is a culmination of the Land We Call Home learning unit which begins the school year and focuses on integrating content across geography, geology, Colorado land regions, ecology, and state history. The trip focuses students on observation and data collection using digital tools across 4 life zones and a 2, 133 meter (7, 000-foot) climb in elevation. A key to field trip success is having students work on a carefully designed field journal before, during, and after the trip. Descriptions of the learning activities and student work samples from field journals provide authentic evidence of the success of the field trip in sparking passionate engagement in learning among students and teachers. Clear connections to the NGSS learning expectations and outcomes are made through narrative and an alignment chart.